Eduardo Scarpetta - Isabella Innamorati (Drammaturgia)
Neapolitan comic actor and prolific author, he was famous with the name of Felice Sciosciammocca. He gained fame as a theatrical reformer for removing traditional masks. He is an essential, sometimes conflicting, reference point in the theatrical formation of his legitimate and illegitimate children: Domenico, Vincenzo, and Maria Scarpetta, as well as Titina, Eduardo, and Peppino De Filippo.